Red Hat Certified System Administrator (RHCSA) complete video course with virtual machines - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Pearson IT Certification, 2017)
"Now with virtual machines and fully updated for RHEL 7.3, Red Hat Certified System Administrator (RHCSA) Complete Video Course with Virtual Machines, Second Edition gives you everything you need to prepare for and pass the RHCSA exam. This engaging self-paced video training solution provides learners with 15 hours of personal visual instruction from an expert trainer with more than 20 years of practical Linux teaching experience. Through the use of topic-focused instructional videos you will gain an in-depth understanding of all topics on the Red Hat Certified Administrator (RHCSA) exam as well as a deeper understanding of Red Hat Enterprise Linux so you master the key foundational principles of systems administration. The combination of video, labs, and virtual machines is a unique offering that gives you a full toolkit to learn and excel on your exam."--Resource description page.
Presenter, Sander van Vugt.
Title from title screen (viewed March 22, 2017).
Keywords: Linux -- Certification -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Systems engineering; Virtual computer systems; Electronic books